DENEYSEL PARSİYEL MESANE ÇIKIM OBSTRÜKSİYONU OLUŞTURULAN TAVŞANLARDA TERAZOSİN VE MELATONİN UYGULAMALARININ, MESANE KONTRAKTİLİTESİ, HİSTOPATOLOJİ VE OKSİDAN/ANTİOKSİDAN SİSTEM ÜZERİNE ETKİLERİ - TAŞDEMİR, CEMAL (Fırat Üniveristesi, 2006)
[Abstract Not Available]
The effects of terazosin and melatonin on the urinary bladder contractility,histopatology and oxidant/antioxidant system in rabbits with experimentally induced partial bladder outlet obstruction.
Keywords: Üroloji